Pembelajaran Humanistik dalam Pengajaran Pertama: Membebaskan Siswa dari Penjara Kebebasan, Menanam Bibit Kosong dan Bibit Keimanan - Ikmal, Happy (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2020)
This paper aims to describe how humanistic learning should be carried out in the first teaching: freeing students from the prison of freedom, a choice of planting empty seeds or seeds of faith. This research is a qualitative literature study to provide a set of insights on how phenomenons are interpreted in the literature. Research design becomes a reflexive process at each stage of the research. Qualitative analysis involves two activities: 1) developing an awareness of the types of data that can be examined and how they can be explained. Finally, social artifacts such as books, sculptures, pictures and buildings can be a unit of analysis. From the results of the discussion it can be concluded as follows: 1) Educating is understanding students so that they can see the real form of reality, rather than the reality projected by an image. Providing noetic experiences as new insights does not increase our quantitative knowledge of objects which remain unchanging, but introduces changes in the modes of knowledge. 2) Liberal education, which is well taught can restore a person's sense of dignity as a human being in the universe and with others, and thus can give students eyes to see the dignity of others by sharing their own difficulties. Well-taught Islamic education raises the inner heart of the child, the seed of faith in Allah critically so that the child is able to count himself, pious, and raise him because he is afraid of Allah while working and takes into account himself when he thinks, and experiences pious feelings, he will be sincere to Allah , Lord of the worlds in all his states and deeds and in all his behavior. And the most important thing is that he will not do anything except to get the Pleasure of Allah.